Health inequities in Bhutan's free healthcare system: a health policy dialogue summary - Karma Tenzin; Thinley Dorji; Gampo Dorji; Don Eliseo Lucero‐Prisno III (Wiley, 2022)
Abstract Bhutan has a free healthcare system that covers almost 90% of the population within 2 h of travel distance. The country has achieved remarkable success in many public health indicators despite the chronic shortage of financial resources and trained manpower. However, there are many aspects of health inequities in the government's health policies, programmes and health services. The Khesar Gyalpo University of Medical Sciences of Bhutan, Thimphu in 2020 hosted a policy dialogue on health equity in the context of the Bhutanese health system. With changing demographics and socioeconomic conditions, some of the factors that earlier determined an equitable distribution of services and resources are no longer relevant now. The referral system is easily bypassed not only because the patients have easy access to transportation to tertiary hospitals, but because of frequent interruptions in the service and the non‐availability of doctors in the district and general hospitals. The role of the private sector is restricted to a few diagnostic services while there is an apparent adequate spending capacity of consumers. There is an important component of out‐of‐pocket expenditure and catastrophic health expenditure in patients seeking treatments outside the country. The current health policies and strategic plans for the future lack a measure of health equity. We recommend conscientious assessment of health inequities in the current system and introducing policies and programmes to prevent the worsening of such inequities.